Percepción del desempeño docente y satisfacción de los estudiantes universitarios de las Ciencias de la Salud de la Universidad Nacional Hermilio Valdizán de Huánuco, 2013 - Deza y Falcon, Irene (2017)
Objective: To determine the relationship between perception of teacher performance and satisfaction of university students in health sciences at the National University of Huanuco Valdizán Hermilio in 2013 . Methods: The design was correlational, prospective, cross-sectional sample consisted of 385 students, who were applied interview guides and inventory of teacher performance, prior informed consent. Statistical analysis was by Spearman Rho contrast, relying on the SPSS V 20.0. Results: Most students demonstrate a level of “ optimal satisfaction “ [ 49.6 % ( 191 )] , followed by those who express a level “moderate satisfaction” [ 46.8 % (180 )] , and “dissatisfaction “ [ 3.6% ( 14 ) ] , respectively . Statistically significant correlation was found between the dynamic class [( Rho = 0.529 ) (p = 0.000) ] , class preparation - compliance program [( Rho = 0.606 ) (p = 0.000) ] , the criteria for assessment - rating [( Rho = 0.595 ) (p = 0.000) ] , respect for students [( Rho = 0.590 ) (p = 0.000) ] , subject mastery [( Rho = 0.610 ) (p = 0.000 )] , student motivation - interpersonal style [( Rho = 0.636 ) (p = 0.000) ] , approach to the profession [( Rho = 0.587 ) (p = 0.000) ] , with college student satisfaction . Conclusions: There is relationship between teacher performance and student satisfaction university, [( Rho = 0.704 ) (p = 0.000) ]